Distributed Three‐Dimensional Formation Containment Control of Multiple Unmanned Aerial Vehicle Systems. Issue 3 (11th January 2017) - Han, Tao; Chi, Ming; Guan, Zhi‐Hong; Hu, Bin; Xiao, Jiang‐Wen; Huang, Yuehua
Abstract: This paper concentrates the distributed formation containment problems for multiple unmanned aerial vehicle (UAV) systems under both fixed directed and switching directed topologies. The objective is to introduce the formation control into the containment control research, where master UAVs should exchange information with each other to achieve and maintain a desired formation. Then, two different control protocols are proposed for the master UAVs and slave UAVs, respectively. Utilizing the algebraic graph theory and stability theory, some sufficient conditions are derived to guarantee the master UAVs complete a prespecified formation, while the states of the slave UAVs converge to a convex hull formed by those of the master UAVs. Finally, some numerical simulations are provided to verify the effectiveness of the theoretical results.